Integration processes in Ukraine: problems and prospects - Дроботова, Людмила Антонівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article the analysis of level of processes of integrations is offered in Ukraine. It is indicated on problemswhich detain the process of integration, questions, related to the prospect of European integration of the Ukrainian economy, joinings of Ukraine, are considered to stranam-uchastnits of the Bolonskogo process.